2018
DOI: 10.1108/meq-03-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of environmental, social, and governance factors on firm performance

Abstract: Purpose-The ESG factor, which consists of environmental, social, and governance factors, represents the non-financial performance of a company. United Nations Principles for Responsible Investment (UN-PRI) invites investors to consider ESG issues when evaluating the performance of any company. Moreover, nowadays the contribution of corporations towards sustainable development is a major concern of investors, creditors, government, and other environmental agencies. Therefore, the purpose of this paper is to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
229
9
48

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(311 citation statements)
references
References 68 publications
25
229
9
48
Order By: Relevance
“…Companies with good corporate governance concepts and have high profitability will be able to show a high stock return for the company. Atan et al (2018) found that there is no significant association between individual factors and the combined ESG and company profitability namely, ROE. The company requires special attention to the environmental conditions in which the company carries out its activities.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Companies with good corporate governance concepts and have high profitability will be able to show a high stock return for the company. Atan et al (2018) found that there is no significant association between individual factors and the combined ESG and company profitability namely, ROE. The company requires special attention to the environmental conditions in which the company carries out its activities.…”
Section: Introductionmentioning
confidence: 92%
“…The most important objective of stakeholder theory and legitimacy theory is assisting manager to understand the stakeholder environment and to manage effectively among the relationships around the companies's environment (Atan et al, 2018). Both stakeholder theory and legitimacy theory can be used to explain why an entity choose to make voluntary disclosures, organizational legitimacy and company disclosures in annual reports as a strategy to maintain the sustainability of the organization.…”
Section: 2mentioning
confidence: 99%
“…Their study brought no significant conclusions establishing a relationship between the variables. ESG was once again explored by Ferrero‐Ferrero, Fernández‐Izquierdo, and Muñoz‐Torres () who sought to explore the effects of ESG consistency on economic performance; Aboud and Diab () who found a positive relationship between ESG quality and firm value; Atan, Alam, Said, and Zamri () who found no relationships for the selected sample; Zhao et al () who analyzed power generation companies; and Xie, Nozawa, Yagi, Fujii, and Managi () who showed that most ESG activities have a nonnegative relationship with financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other accounting variables used for financial performance were 3‐year average profit value (Younis et al, ); growth rate of sales (Tan et al, ); average month revenues (Lucato et al, ); revenue, profit, and rate trend (Oh et al, ); asset to total debt ratio (Paun, ); and weighted average cost of capital (Atan et al, ).…”
Section: Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation